A meta-analytical review of brain activity associated with intertemporal decisions: Evidence for an anterior-posterior tangibility axis. (March 2018) - Smith, Benjamin J.; Monterosso, John R.; Wakslak, Cheryl J.; Bechara, Antoine; Read, Stephen J.
Graphical abstract: Highlights: Levels of abstraction in the prefrontal cortex increase from posterior to anterior. Later choices are processed anterior of Sooner choices in the prefrontal cortex. The effect was primarily observable in the lateral prefrontal cortex. Functional organization of the PFC could form a basis for construal level theory. Abstract: In temporal discounting experiments, subjects are repeatedly presented with option sets in which they must choose between receiving a small amount of money sooner (SmallerSooner) or a larger amount of money at a more distant point in time (LargerLater). Although over 50 temporal discounting experiments using fMRI are described in literature, there has not been a meta-analysis identifying regions activated when subjects choose SmallerSooner versus LargerLater alternatives. Evidence suggests a prefrontal cortex 'abstraction hierarchy', from abstract planning in more anterior regions to concrete processing in posterior regions. Because abstraction has been linked with making LargerLater choices, we hypothesized an association between LargerLater choices and more anterior prefrontal cortex activity, and an association between SmallerSooner choices and more posterior activity. Across thirteen fMRI temporal discounting studies including 436 subjects, we observed LargerLater activity anterior of SmallerSooner activity, both in the left inferior frontal gyrus pars triangularis, consistent with our pre-registered hypothesis. We call for further work linking temporal discounting and hierarchical processing of abstract and concrete information in the prefrontal cortex.